Potrzebuje na szybko
![Potrzebuje Na Szybko class=](https://pl-static.z-dn.net/files/dfd/685f8f87340e9de6b053eff499d8407f.jpg)
Odpowiedź:
1) -(x-2)-[x-(5-2x)]-5x= -x+2-[x-5+2x]-5x= -x+2-[3x-5]-5x= -x+2-3x+5-5x= -9x+7
2) -x-(2-x)-(5-2x)-5x= -x-2+x-5+2x-5x= -3x-7
3) -(x-2)-[x-(5-2x)-5x]= -x+2-[x-5+2x-5x]= -x+2-[-2x-5]= -x+2+2x+5=x+7
4) -x-[2-(x-5)-2x]-5x= -x-[2-x+5-2x]-5x= -6x-[7-3x]= -6x-7+3x= -3x-7
5) -[x-(2-x)-(5-2x)]-5x= -[x-2+x-5+2x]-5x= -[4x-7]-5x= -4x+7-5x= -9x+7
Szczegółowe wyjaśnienie:
odp.Pary równych wyrażeń to:
1 i 5
2 i 4